Decreased Rivaroxaban Levels in a Patient with Cerebral Vein Thrombosis Receiving Phenytoin - Ana F. Becerra; Tomas Amuchastegui; Aldo H. Tabares (Case Reports in Hematology)
Combined use of antiepileptic drugs and anticoagulants is common. We describe the first case documenting laboratory interaction between rivaroxaban and phenytoin. A 48-year-old woman was admitted to our hospital due to cerebral venous thrombosis, bilateral pulmonary embolism, and deep vein thrombosis. She came from a small town with difficult access to warfarin monitoring. She was receiving phenytoin 100 mg three times daily (t.i.d.) and started enoxaparin 60 mg twice daily (b.i.d.). An abdominal mass was diagnosed and removed by laparoscopy (gastrointestinal stromal tumor). On day 5, she was switched to rivaroxaban 15 mg b.i.d. First peak anti-Factor Xa was 70 ng/ml (reference value: 100–300 ng/ml). She was discharged on rivaroxaban 15 mg b.i.d. and phenytoin 100 mg t.i.d. A week later, anti-Xa levels were 90 ng/ml. Due to concerns about thrombosis progression, she was switched to dabigatran. During follow-up, she remained asymptomatic and thrombin time >180 s was measured several times along 3 months as surrogate for dabigatran activity. Phenytoin is a combined CYP3A4 and P-glycoprotein inducer, which might reduce rivaroxaban levels. Dabigatran is substrate of P-glycoprotein, meaning potential malabsorption. Despite unavailability of plasmatic dabigatran essays, our patient improved her symptoms without further symptomatic thromboembolism. Facing these interactions, either monitoring serum levels of anticoagulants or other therapeutic options should be considered.